Perancangan Gedung Hotel 4 lantai di Daerah Solo Baru, Sukoharjo dengan Sistem Rangka Pemikul Momen Menengah - Sulistyo, Dhevid; , Ir. Ali Asroni, MT (2016)
Sukoharjo regency is one of the growing areas in terms of economy and tourism. With respect to the development of the supporting infrastructure requires to meet the needs of temporary accommodation of travellers, the hotel is one of the solutions to meet those needs. The purpose of this final task is to plan the structure of the building 4 floor frame system with Secondary Moment Resisiting Frame (SMRF) in the area of Sukoharjo. Planning the structure refers to the SNI 1726-2012 (the rules of building structure earthquake for building structure and non-structure) and the SNI 2847-2013 (requirenment of concrete structural for building structure). Data planning includes land site classification categories SC (the ground hard), earthquake resistant building with response modification factor (R) by virtue of building factor 5, Ie with a value of 1.0. The quality of concrete used f'c 25 MPa, as well as longitudinal reinforcement fy = 350 MPa and shear reinforcement (begel) fyt = 320 MPa. Calculating the forces within SAP applications using SAP2000 and to draw the results of calculations using the AutoCAD application. The results of the calculation produces a thick 12 cm for floor slab and roof slabs with a thickness of 10 cm and 15 cm. For the main structure of the beams were obtained with dimensions 300/400 and column with dimensions 300/400, for bottom structure using continuous foundation and sloof with dimensions 400/1000 with soil bearing capacity = 125 kPa at a depth of -2.0 m.